A sub-utilização dos opióides na dor oncológica - Gonçalves, Ferraz (1995)
Pain is a frequent problem with major injluence in the quality of life of oncologic patients. Opioids, specially morphine, have a main importance in pain treatment, but the secundary place it has in the tea ching of medicine, makes they are incorrectly used. Myths, popular among patients, about oncologic pain and analgesics, often makes them relutant in reporting pain and adhering treatment. It is of utmost importance to prescribe opioids apropriatelly and discuss with patients the need of using them as well as their side effects, avoiding the injustifible suffering of many of those patients.